2017
DOI: 10.5530/jyp.2017.9.12
|View full text |Cite
|
Sign up to set email alerts
|

Study of adverse drug effects of antiepileptic drugs used in pediatric patients in a tertiary care rural hospital – a Pharmacovigilance study

Abstract: Objective: To assess the prescription pattern & Adverse Drug Reaction (ADR)) profile of Antiepileptic drug (AEDs) therapy in children of rural population. Materials and Methods: This prospective open label, observational study was carried out over one and half year duration on 142 newly diagnosed epileptic children below 12 yrs age receiving AEDs in pediatric department in a tertiary care rural hospital. Follow up was done every month for 6 months duration. Prescription pattern and incidence, causality and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…According to Singh et al, Distribution of ADRs across therapeutic classes were Antimicrobials (28.57%), antihypertensive's (24.02%), anti-diabetics (14.28%), and NSAIDs (9.74%). [30][31][32] According to Tiwari et al, gastrointestinal system (73%) was found to be the most commonly affected organ system, followed by the metabolic (17%), cutaneous system (5%), haematological system (3%) and cardiovascular system (2%). 21 In our study also it was quite evident that GI (38%), ADRs are the highest followed by dermatologic (23.3%), metabolic (9.33%), CNS (8%), CVS (7.3%), renal (4%) and musculoskeletal (1.33%).…”
Section: Incidence Of Antibiotic Classesmentioning
confidence: 99%
“…According to Singh et al, Distribution of ADRs across therapeutic classes were Antimicrobials (28.57%), antihypertensive's (24.02%), anti-diabetics (14.28%), and NSAIDs (9.74%). [30][31][32] According to Tiwari et al, gastrointestinal system (73%) was found to be the most commonly affected organ system, followed by the metabolic (17%), cutaneous system (5%), haematological system (3%) and cardiovascular system (2%). 21 In our study also it was quite evident that GI (38%), ADRs are the highest followed by dermatologic (23.3%), metabolic (9.33%), CNS (8%), CVS (7.3%), renal (4%) and musculoskeletal (1.33%).…”
Section: Incidence Of Antibiotic Classesmentioning
confidence: 99%
“…The finding that CNS related ADRs is maximum correlates with other studies. 9,21 Headache (82.35%) was maximum reported symptom followed by drowsiness which was unlike other study conducted by Suman et al where sedation was the most frequent ADR i.e. 11.2% of total ADRs.…”
Section: Discussionmentioning
confidence: 67%
“…11.2% of total ADRs. 9 This difference in CNS related symptoms can be due to the variation in study population and site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in the North India by Suman and Gosavi reported similar finding. [ 23 ] Interestingly, both of these tablets were special dosage forms (enteric and film-coated).…”
Section: Discussionmentioning
confidence: 99%